2022
DOI: 10.1007/s43630-022-00172-9
|View full text |Cite
|
Sign up to set email alerts
|

An organometallic approach for the preparation of Au–TiO2 and Au-g-C3N4 nanohybrids: improving the depletion of paracetamol under visible light

Abstract: The photocatalytic degradation of paracetamol (a common analgesic also known as acetaminophen) in ultrapure water with different photocatalytic systems was performed under ultraviolet or visible irradiation. The photocatalysts employed were: commercial Degussa-P25 TiO2 and Au–TiO2 under UVA irradiation (365 nm) and g-C3N4 and Au-g-C3N4 under visible light irradiation (low-power (4 × 10 W) white light LEDs), improving the effectiveness of degradation rates when the gold nanoparticles (Au NPs) were combined with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 41 publications
(41 reference statements)
0
5
0
Order By: Relevance
“…However, the photocatalytic activity of g-C 3 N 4 is still low. In order to solve the problem, many methods, including synthesis techniques, nanostructure design and electronic structure modulation have been proposed, in order to improve the photocatalytic performance of g-C 3 N 4 [13][14][15]. Among them, deposition of efficient alternative semiconductors onto g-C 3 N 4 has proven to be a feasible and effective measure to enhance its photocatalytic activity and efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…However, the photocatalytic activity of g-C 3 N 4 is still low. In order to solve the problem, many methods, including synthesis techniques, nanostructure design and electronic structure modulation have been proposed, in order to improve the photocatalytic performance of g-C 3 N 4 [13][14][15]. Among them, deposition of efficient alternative semiconductors onto g-C 3 N 4 has proven to be a feasible and effective measure to enhance its photocatalytic activity and efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, attention has focused on its removal from aqueous media following a photocatalysis approach, as described below. 79–147…”
Section: Removal Of Pharmaceutical Components Using Different Photoca...mentioning
confidence: 99%
“…In view of this, several studies have been reported on the photodegradation of pharmaceutical pollutants in metal-loaded metal oxides. Jiménez-Salcedo et al 87 applied an organometallic approach for the preparation of Au-TiO 2 nanohybrids and studied the degradation of paracetamol (0.3 mg L −1 ) under UVA light. These studies revealed 100% degradation of paracetamol in 30 min for Au-TiO 2 photocatalysts compared to TiO 2 (40 min).…”
Section: Rsc Applied Interfaces Reviewmentioning
confidence: 99%
“…In this regard, we have developed an organometallic approach for the synthesis of size and shape-controlled Au and AuAg NPs of different sizes and shapes by the reduction of pentafluorophenyl precursors [Au(C 6 F 5 )(tht)] (tht = tetrahydrothiophene) [ 27 ] and [Au 2 Ag 2 (C 6 F 5 ) 4 (OEt 2 ) 2 ] n [ 28 ], respectively. The formation of Au and AuAg NPs from these precursors has also allowed the synthesis of very efficient plasmonic photocatalysts for the depletion of persistent drugs in wastewater, through the formation of the metal NPs at the surface of semiconductor carbon nitride 2D nanosheets [ 29 , 30 ], or for photocatalytic dehydrogenation of NH 3 ·BH 3 and H 2 release using wavy AuAg nanorods [ 31 ]. Following this idea and given the excellent photothermal properties of MoS 2 , we wondered whether the inclusion of bimetallic AuAg NPs of small size, which are superior catalysts in the transformation of 4-NP to 4-AP, would produce a new type of hybrid material in which a synergistic effect between the photothermal heating produced at MoS 2 NFs would increase, even more, the efficiency of the grafted AuAg NPs in the catalytic reduction of 4-NP.…”
Section: Introductionmentioning
confidence: 99%